Nitrosyl Complexes in Inorganic Chemistry, Biochemistry and Medicine I - Mingos, D. Michael P. (Structure and Bonding, 2014)
D. Michael P. Mingos Historical Introduction to Nitrosyl Complexes Hanna Lewandowska Coordination Chemistry of Nitrosyls and Its Biochemical Implications Hanna Lewandowska Spectroscopic Characterization of Nitrosyl Complexes Yanfeng Jiang, Heinz Berke Nitrosyl Complexes in Homogeneous Catalysis.